PENDIDIKAN PENDERITAAN DALAM KITAB AYUB GUNA MEMBERI SOLUSI PERKARA-PERKARA DUNIA PELAYAN TUHAN - Iis Dahlia Mayasari; Chearolina Chearolina; Suryowati Wang (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2020)
Abstract: Suffering is pressure that comes from outside a person. The suffering that exists in humans is both unavoidable and inevitable. The problem that arises is: What is meant by suffering education? How to provide a solution to the suffering of people who are complaining? How to provide a solution to the suffering of the quarreling person? How to provide a solution to the suffering of those who commit suicide? How does the education of suffering in the book of Ayub provide solutions to the things of God's servant world at GBI KelIR Samarinda? The answer: (1) Education for suffering is education to live in the world. Humans as God's creation still accept every suffering that comes in their life. (2) The solution to the suffering of a complaining person is: do something happily, have a heart that is willing to accept criticism and suggestions, still give thanks to God, and be humble. (3) The solution to the suffering of the quarreling person is: don't always feel right, apologize first when you are guilty, learn to yield, and be willing to listen to advice. (4) The solution to the suffering of a person who commits suicide is someone who dares to live in pain and can accept the reality of life, is obedient to God, is always grateful, and always longs to live in historical peace. (5) The education of suffering taught to God's servants at GBI KelIR Samarinda is: Education continues to survive, Education to Realize God is the Source of Life, Education Do not Blame Anyone, and Education "makes people aware that suffering is a test and not everything comes from sin". Abstrak: Penderitaan adalah tekanan yang datang dari luar diri seseorang. Penderitaan yang ada pada manusia tidak bisa ditolak dan tidak bisa dihindari. Persoalanya yang muncul adalah: Apakah yang dimaksud dengan pendidikan penderitaan? Bagaimanakah memberi solusi tentang penderitaan  orang yang bersungut-sungut? Bagaimanakah memberi solusi tentang penderitaan orang yang bertengkar?  Bagaimanakah memberi solusi tentang penderitaan orang yang bunuh diri? Bagaimanakah pendidikan penderitaan dalam kitab Ayub memberi solusi perkara-perkara dunia pelayan Tuhan di GBI KelIR Samarinda? Jawabnya: (1) Pendidikan penderitaan adalah pendidikan untuk hidup di tengah dunia. Manusia sebagai ciptaan Allah tetap menerima setiap penderitaan yang datang dalam kehidupannya. (2)  Solusi tentang penderitaan  orang yang bersungut-sungut adalah: melakukan suatu hal dengan senang hati, memiliki hati yang mau menerima kritik dan saran, tetap mengucap syukur kepada Tuhan, dan rendah hati. (3) Solusi tentang penderitaan orang yang bertengkar adalah adalah: jangan merasa selalu benar, meminta maaf terlebih dahulu ketika bersalah, belajar mengalah, dan mau mendengar nasihat.  (4) Solusi tentang penderitaan orang yang bunuh diri adalah seseorang berani hidup menderita dan dapat menerima kenyataan hidup, taat kepada Tuhan, selalu bersyukur, dan selalu rindu hidup damai sejarah. (5) Pendidikan penderitaan  yang diajarkan kepada pelayan  Tuhan di GBI KelIR Samarinda adalah: Pendidikan tetap Bertahan, Pendidikan Menyadari Allah adalah Sumber Hidup, Pendidikan Jangan Menyalahkan Siapapun, dan Pendidikan “menyadarkan bahwa penderitaan adalah sebuah ujian dan tidak semuanya berasal dari dosa”.